Comparing lensing and stellar orbital models of a nearby massive strong-lens galaxy. Issue 4 (22nd March 2022) - Poci, Adriano; Smith, Russell J
ABSTRACT: Exploiting the relative proximity of the nearby strong-lens galaxy SNL-1, we present a critical comparison of the mass estimates derived from independent modelling techniques. We fit triaxial orbit-superposition dynamical models to spatially resolved stellar kinematics, and compare to the constraints derived from lens modelling of high-resolution photometry. From the dynamical model, we measure the total (dynamical) mass enclosed within a projected aperture of radius the Einstein radius to be log10 ( M Ein /M⊙ ) = 11.00 ± 0.02, which agrees with previous measurements from lens modelling to within $5{\rm {per\ cent}}$ . We then explore the intrinsic (de-projected) properties of the best-fitting dynamical model. We find that SNL-1 has approximately constant, intermediate triaxiality at all radii. It is oblate like in the inner regions (around the Einstein radius) and tends towards spherical at larger radii. The stellar velocity ellipsoid gradually transforms from isotropic in the very central regions to radially biased in the outskirts. We find that SNL-1 is dynamically consistent with the broader galaxy population, as measured by the relative fraction of orbit 'temperatures' compared to the CALIFA survey. On the mass–size plane, SNL-1 occupies the most-compact edge given its mass, compared to both the MaNGA and SAMI surveys. Finally, we explore how the observed lensing configuration is affected by the orientation of the lens galaxy. We discuss the implications of such detailed models on future combined lensing and dynamical analyses.